(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model on students’ critical thinking skills in basketball lessons at SMA Negeri 5 Makassar. The study used a quasi-experimental design with a pretest-posttest control group pattern involving 40 students, consisting of 20 in the experimental group and 20 in the control group. The instrument used was a critical thinking ability test based on the context of a basketball game. The results showed that the experimental group, who received PBL learning, experienced a significant increase in their critical thinking scores, from an average pretest score of 56.40 to 82.75 on the posttest, a difference of 26.35 points. Meanwhile, the control group, which received conventional learning, only experienced an increase from 55.85 to 68.10, a difference of 12.25 points. Paired sample t-test analysis showed significant improvement in both groups, but the experimental group’s improvement was significantly greater (t = 12.85; p = 0.000) than the control group’s (t = 6.14; p = 0.000). The independent sample t-test results showed a significant difference in critical thinking skills improvement between the experimental and control groups (t = 7.21; p = 0.000). The effect size value of 2.15 indicates that the influence of the PBL model is categorized as very large. Thus, this study confirms that the PBL model is an effective learning approach in improving students’ critical thinking skills, especially in the context of sports learning based on problem-solving and tactical analysis of games.